An Analytical Study Of Traffic Accidents In The City Of Erbil In The Period 1979-2019 - Omed Abdulmajid Qader; Tahir Hasso Zebri (QALAAI ZANIST JOURNAL, 2020)
An analytical study of traffic accidents in the city of Erbil in the period 1979-2019 With traffic accidents turning into a major concern for all members of society, And what has been accomplished from that, which has undergone several financial and human resources in the city of Erbil.Erbil city is one of the Kurdistan Region cities,which the largest number of traffic accidents are registered in it.In the light of the professional role, media plays an effective partner in disseminating traffic culture and achieving awareness and prevention among all groups of society. The media with all its written, audio, and visual means is concerned with traffic awareness issues and preventing traffic accidents through various activities amid creating traffic awareness for drivers, as well as adopting proper behavior while driving the vehicles in order to reduce the number of traffic accidents in the city.